Power Consumption Analysis of ONT (Optical Network Ter-minal) Devices in Indihome Household Usage - Amos Marganda Girsang; Ahmad Dani; Solly Aryza (Sean Institute, 2025)
Optical Network Terminal (ONT) devices are the main components in the Fiber to the Home (FTTH) network used by IndiHome to provide fiber optic-based internet services. ONT operates continuously for 24 hours, so the power consumption of this device contributes to household electricity use. In this final project aims to analyze ONT power consumption under various operational conditions and identify its effect on household electricity loads. The research method includes measuring ONT power consumption using a wattmeter in three usage scenarios: idle (no connected devices), normal (1-3 connected devices), and high load (more than 3 active streaming/gaming devices). Data were collected over several days to identify power consumption patterns. Utilization of power saving modes (if available), and selection of ONTs with better energy efficiency. The results of this study are expected to provide insights for IndiHome users to improve energy efficiency in internet use in households.